Building a Literate Generation: The Role of Teachers in Diagnosing and Developing Reading Literacy among Students at the Indonesian School in Jeddah - Adi Atmoko; Ade Eka Anggraini; Khusnul Khotimah; Irene Milenia Siki; Santy Dinar Permata; Oriza Zativalen (Universitas Muhammadiyah Surakarta, 2025)
This program aims to improve students' reading literacy by strengthening teachers' professional competencies in conducting relevant and contextual diagnostic assessments of reading difficulties in multilingual and multicultural environments. The main challenges in the field are teachers' lack of understanding of effective diagnostic assessment concepts and methods, as well as the limited availability of structured assessment tools. In the context of globalization, reading skills are a major factor in students' academic success and adaptation. This activity includes seminars, theoretical and practical training, and assistance in developing valid and reliable diagnostic instruments. The community service activity was held on August 3 to 7, 2025, involving 40 teachers from various educational backgrounds. Teachers were trained to accurately identify students' reading difficulties so that learning interventions could be designed in a targeted and sustainable manner. The results of this activity showed an increase in teachers' understanding of the concept of diagnostic assessment and higher student reading motivation. Teachers acquired practical skills in developing and using diagnostic instruments that can be used on an ongoing basis. This increase in competence is expected to strengthen the position of schools as adaptive and data-driven educational institutions. Thus, this program can make a real contribution to improving the quality of reading literacy and supporting the sustainable development of international education in Indonesian schools abroad.